2014
DOI: 10.1177/0300060513492484
|View full text |Cite
|
Sign up to set email alerts
|

Association between phospholipase C epsilon gene (PLCE1) polymorphism and colorectal cancer risk in a Chinese population

Abstract: Objective: To investigate the association between a single nucleotide polymorphism rs2274223 (adenine [A] to guanine [G]) in the phospholipase C epsilon 1 (PLCE1) gene and susceptibility to colorectal cancer (CRC). Methods: The PLCE1 rs2274223 polymorphism was genotyped in patients with CRC and age-and sex-matched cancer-free control subjects from a Chinese population in a case-control study. PLCE1 mRNA levels in pair-matched tumour and adjacent noncancerous tissue were evaluated by real-time quantitative reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…A case-control research including 417 CRC patients and 416 controls reported that carriers of AG and GG genotypes had an increased risk for CRC. This study also showed that lower levels of PLCE1 mRNA were observed both in carriers of AG and GG genotypes (Wang et al, 2014). Similar results were obtained in a study by Li and colleagues which reported a sigificant association between rs2274223 and CRC (Li et al, 2012b).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A case-control research including 417 CRC patients and 416 controls reported that carriers of AG and GG genotypes had an increased risk for CRC. This study also showed that lower levels of PLCE1 mRNA were observed both in carriers of AG and GG genotypes (Wang et al, 2014). Similar results were obtained in a study by Li and colleagues which reported a sigificant association between rs2274223 and CRC (Li et al, 2012b).…”
Section: Discussionsupporting
confidence: 90%
“…Since different cancers may share common pathogenetic pathways (Bunney and Katan, 2006), we hypothesized that SNPs that have been implicated in other gastrointestinal carcinomas may also play a role in CRC development. To date, there are very few papers which have assessed this relationship in CRC patients (Li et al, 2012b;Smith et al, 2012;Wang et al, 2014). Furthermore, to our best knowledge this is the first report aimed at evaluating the role of rs4072037 and rs2274223 for CRC development in European population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the study conducted by Ezgi et al (controls: n=210, colorectal tumor: n=200) clearly showed that rs2274223 SNP was associated with higher risk of colorectal cancer development in Turkish and Caucasian people 50. Interestingly, the study of Wang and coauthors demonstrated that rs2274223 A>G change might decrease level of PLCE1 expression and the variant G phenotype is associated with a high susceptibility to colorectal cancer in Chinese population (controls: n=416, colorectal tumor: n=417) 51. Later, Zhang et al performed a study of multiple PLCE1 SNPs for their potential correlation with a high risk of colorectal cancer development in Han Chinese population (controls: n=385, colorectal tumor: n=276).…”
Section: Digestive Tract Cancersmentioning
confidence: 99%